Lives turned upside down in COVID-19 times: exploring disabled people's experiences in 5 low-and-middle income countries using narrative interviews - Wickenden, Mary; Shaw, Jackie; Thompson, Stephen; Rohwerder, Brigitte (Disability Studies Quarterly, 2021)
This article explores COVID-19 related experiences of disabled people in Bangladesh, Kenya, Nigeria, Nepal and Uganda. Narrative interviews generated storied responses, focussing on respondents' priorities, which enabled us to hear what was most significant for them and their families. 143 interviews were conducted online or by phone by 7 local researchers (3 disabled), with appropriate inclusive support. Nearly everyone was interviewed twice to capture the progression of impacts over time. The data was analysed thematically through a virtual participatory approach. An overarching 'subjective' theme of feelings experienced by the participants was labelled 'destabilisation, disorientation and uncertainty'. We also identified 'concrete' or material impacts. People experienced various dilemmas such as choosing between securing food and keeping safe, and tensions between receiving support and feeling increased vulnerability or dependence, with interplay between the emotions of fear, loss and hope. We found both the concept of liminality and grief models productive in understanding the progression of participants' experiences. Disabled people reported the same feelings, difficulties and impacts as others, reported in other literature, but often their pre-existing disadvantages have been exacerbated by the pandemic, including poverty, gender and impairment related stresses and discrimination, inaccessible services or relief, and exclusion from government initiatives.